Intensi Migrasi Nasabah Emerging HNWI Pasca Pergantian Relationship Manager pada Perbankan Non-Metropolitan - Mukhlis Purnama Hadi (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2026)
Banks' Relationship Manager (RM) rotation policies conceal a retention risk: premium customers loyal to individual RMs may migrate following replacement triggered by relational disruption, not service failure. This conceptual study builds a theoretical framework explaining Emerging HNWI customer migration intention following RM turnover, integrating three antecedents adapted from the Service Provider Switching Model (SPSM): Relational Embeddedness (RE) as a mooring factor, Relational Trust toward the former RM (RT) as a paradoxical push factor through the Relational Loss Effect mechanism, and Community-Validated Trust (CVT) as the primary migration inhibitor. CVT is conceptualized as trust formed prior to direct interaction through personal communal validation distinct from reputation trust, social trust, swift trust, and social proof. Three boundary conditions of CVT are explicitly identified for testability and cross-context comparison. Primary contributions: (1) CVT as a SPSM extension for relational disruption contexts; (2) Relational Loss Effect bridging trust theory and paradoxical migration behavior.